Ovarian Stem Cells Differentiation into Primary Oocytes Using Follicle Stimulating Hormone, Basic Fibroblast Growth Factor, and Neurotrophin 3 - S Tanbakooei; SMA Haramshahi; G Vahabzadeh; M Barati; M Katebi; F Golab; Q Shetbi; N Niknam; L Roudbari; M Rajabi Fomeshi; S Amini Moghadam (JRI, 2021)
Background: In vitro obtaining oocytes can be an appropriate alternative for patients with gonadal insufficiency or cancer survivors. The purpose of the current research was isolating stem cells from ovarian cortical tissue as well as evaluating the effectiveness of follicle stimulating hormone (FSH), basic fibroblast growth factor (bFGF), and neurotrophin 3 (NT3) in differentiating to oocyte-like cells. Methods: A human ovary was dissected and cortical tissue pieces were cultured for cell isolation. Isolated cells were divided into 8 groups (3 cases in each group) of control, FSH, NT3, bFGF, FSH+NT3, FSH+bFGF, NT3+bFGF, and FSH+NT3+ bFGF. Pluripotency specific gene (OCT4-A and Nanog), initial germ cells (c-KIT and VASA) and PF growth initiators (GDF-9 and Lhx-8) were evaluated by qRT-PCR. Experiments were performed in triplicate and there were 3 samples in each group. The results were analyzed using one-way ANOVA and p-value less than 0.05 was considered statistically significant. Results: Flow cytometry results showed that cells isolated from the ovarian cortex expressed markers of pluripotency. The results showed that the expression of Nanog, OCT4, GDF-9 and VASA was significantly increased in FSH+NT3 group, while treatment with bFGF caused significant expression of c-KIT and Lhx-8 (p<0.05). Also, according to the results, isolated cells treated with NT3 significantly increased c-KIT expression. Conclusion: According to our results, the ovarian cortex cells could be differentiated into primordial follicles if treated with the proper combination of FSH, bFGF, and NT3. These findings provided a new perspective for the future of in vitro gamete proudest.